METHODOLOGICAL SUPPORT OF INTERCULTURAL COMMUNICATION OF STUDENTS IN ENGLISH LESSONS - Boichuk, Valentyna; Zhelanova, Viktoriia (The Modern Higher Education Review, 2022)
The article is devoted to the methodological support for the formation of intercultural communication of school students in English lessons. The aim of the article is to describe the methodological support which can be used to form the intercultural communication of school students at the English lessons. Analysis and systematization of the methods for the formation of intercultural communication of school students at the English lessons were chosen as the leading methods. The author mentions that in the era of globalization and digital society the development of science, technology and pace of people’s life is constantly accelerating. Thus, nowadays, one of the most necessary skills of a modern person is his or her readiness for the intercultural communication, which supposes his or her ability to communicate with the representatives of different cultures and to achieve the desired result – mutual understanding. It is pointed out that the secondary school has to form the readiness for intercultural communication since adolescence. This age is sensitive to the formation of moral and cultural qualities of personality, character, attitudes, stereotypes of behaviour thinking, world-view which provides an opportunity to instil national and universal human values in teenagers, to cultivate a respectful attitude towards another culture. Also, the most favourable environment for acquiring and learning international communication skills is the English lesson. It is almost impossible to communicate with the representatives of other cultures without knowing English. It is defined that the effective methodological support for the formation of intercultural communication of school students at the English lessons depends on the correct usage, combination and sequence of methods, techniques and means. Different methods of forming intercultural communication of school students at the English lessons are given: verbal narrative, clarification, discussion, lecture, illustration method, displaying, dramatization method, dialogic teaching and technologies, simulations and interactive simulation methods, methods of biographic reflection, role plays, method of projects, WebQuests, training method.